PKM PELATIHAN MEMBUAT KONTRAK SEDERHANA UNTUK PENGERJAAN PENGECATAN DI SMKN 26 JAKARTA - Darmawan Pontan; Muhammad Sapto Nugroho; Ulfa Fatmasari Faisal; Martinus Bambang Susetyarto; Andre Tampubolon (Yayasan Education and Social Center, 2026)
This community service program (PKM) aims to enhance the professional competence of SMKN 26 Jakarta students in construction project management, specifically regarding the planning and legal aspects of painting works. The primary focus of this activity is to introduce the significance of simple work contracts as a legal protection instrument for all parties and to equip students with technical project control skills. The implementation method was divided into three main sessions: (1) teaching project contract concepts and theories, (2) practical training on creating simple contracts using structured forms, and (3) a tutorial on utilizing Artificial Intelligence (AI) for administrative and planning efficiency. Data were collected from 63 respondents through pre-test surveys and post-test evaluations. The results indicate highly significant program effectiveness, where post-training, the practical ability of students to develop project control instruments such as Bar-Charts and S-Curves reached 100%. The integration of AI technology proved to accelerate students' understanding in accurately preparing estimates and contract documents. The conclusion of this activity is that students now possess better readiness to enter the construction industry workforce, equipped with risk management, contract legality, and professional quality control capabilities